THE SECRETION OF DIGESTIVE ENZYMES AND CAECAL SIZE ARE DETERMINED BY DIETARY PROTEIN IN THE CRICKET Gryllus bimaculatus. Issue 3 (22nd July 2016) - Woodring, Joseph; Weidlich, Sandy
Abstract : In Gryllus bimaculatus, the size of the caecum decreases in the latter half of each instar to a stable minimal size with a steady minimal rate of digestive enzyme secretion until feeding resumes after ecdysis. The higher the percent protein in the newly ingested food, the faster and larger the caecum grows, and as a consequent the higher the secretion rate of trypsin and amylase. When hard boiled eggs (40% protein) are eaten the caecum is 2× larger, the trypsin secretion is almost 3× greater, and amylase 2.5× greater then when fed the same amount of apples (1.5% protein). Only dietary protein increases amylase secretion, whereas dietary carbohydrates have no effect on amylase secretion. The minimal caecal size and secretion rate must be supported by utilization of hemolymph amino acids, but the growth of the caecum and increasing enzymes secretions after the molt depend upon an amino acid source in the lumen. This simple regulation of digestive enzyme secretion is ideal for animals that must stop feeding in order to molt. This basic control system does not preclude additional regulation mechanisms, such as prandal, which is also indicated for G. bimaculatus, or even paramonal regulation.